Episodic Sustainability Narratives & Ephemeral Awareness in Fast Fashion: Social Listening Insights - Azhar, Ratih Mukti (Cita konsultindo, 2026)
The discourse on sustainability within the fast fashion industry often finds itself trapped in a paradox between massive information volume and the actual depth of public engagement. This study aims to analyze the dynamics of sustainability narratives in the digital space, focusing on the phenomenon of episodic narratives and platform amplification effects. Utilizing a social listening method via the Brand24 platform, this research gathered a dataset of 19,378 mentions, reaching an accumulated digital audience of 97 million during the period of December 2025 to January 2026. The results indicate a